IOC seeks Covid vaccines for athletes in second wave so Olympics can go ahead (The Guardian, 2021)
The International Olympic Committee is working on ways to get athletes the coronavirus jab in the second or third wave so that the Tokyo Games can go ahead safely in July, the Guardian has been told.